1991
DOI: 10.1111/j.1365-2648.1991.tb03430.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' rights and the admission and discharge process

Abstract: This study examines what patients' admission to and discharge from hospital means for nurses in their relations with patients. The study focuses on the rights of patients and the rights and duties of nurses working in a general hospital and in the community. The 'information standard' is introduced, consisting of three conceptions: informed consent, informed referral and informed discharge. In-depth interviews have been conducted with patients (n = 11) and nurses (n = 22) to elucidate views on and personal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…1991). On the other hand, some studies have shown that patients themselves regard that they have received sufficient information (Dawes & Davison 1994; Klop et al. 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1991). On the other hand, some studies have shown that patients themselves regard that they have received sufficient information (Dawes & Davison 1994; Klop et al. 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Klop et al. (1991), patients ( n = 11) had no complaints about the information given by nurses during the hospital admission and discharge process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Home care referral communication was equally important in initiating as well as reinstating services (Williams, Greenwell, & Groom, 1992). Written and verbal information exchange and patients' understanding of information were factors in communications (Klop, Van Wijmen, & Philipsen, 1991). Community nurses often were not informed about hospital admissions during home care, and inadequate exchange of information resulted in unsuitable arrangements.…”
Section: Communicationmentioning
confidence: 99%
“…The problems of discharging patients from hospital have been well documented in the literature over the last 20 years ( Brown, 1990; Klop, 1991; Armitage, 1994; McBride, 1995). Tierney (1993) outlines some of the shortcomings of hospital discharge arrangements found in the literature.…”
Section: Introductionmentioning
confidence: 99%